The Interplay Between Regulation and Competitions: The Case of Universal Service Obligations - Steffen H. Hoernig; Tommaso M. Valletti (Center for Economic Studies and ifo Institute (CESifo), 2002)
Regulators have long been aware of the social aspects of communication. In the past, regulated monopolists have provided Universal Service Obligations, typically funded via a system of cross-subsidies. In this paper, we first review the rationale for imposing Universal Service Obligations, based both on theoretical arguments and empirical results. We then address some of the new questions raised by the ongoing liberalisation process. Regulators now face the challenging problem of organising the provision and financing of universal service in a competitive environment.
Keywords: 330; universal service obligations; regulation; competition